Exploring the Determinants of Diabetic Foot Ulcer Healing: A 12-Month Longitudinal Study - Hanan Ansari; Intan Habibi; Munafirah Munafirah (Indonesian Science Media, 2025)
Background: Diabetic foot infections (DFI) are a major complication of diabetes mellitus, contributing significantly to morbidity, amputation, and mortality. The healing process of diabetic foot ulcers (DFU) is influenced by multiple factors, including glycemic control, smoking status, and comorbidities such as neuropathy and peripheral artery disease. While cross-sectional studies have explored these factors, longitudinal studies are needed to observe how these variables affect the healing process over time. Purpose: To identify clinical, demographic, and lifestyle factors that influence the healing of diabetic foot infections over 12 months in patients at Hospital Nurhayati Garut. Methods: This prospective longitudinal study included 130 diabetic patients diagnosed with type 1 or type 2 diabetes mellitus and a diabetic foot ulcer of Wagner grade 2 or higher. Patients were followed over 12 months with data collection at baseline, 3, 6, and 12 months. Variables collected included demographics (age, sex), clinical characteristics (glycemic control, smoking status, infection severity, comorbidities), and treatment regimens. Kaplan-Meier survival analysis, Cox proportional hazards regression, and Generalized Estimating Equations (GEE) were used to analyze predictors of wound healing. Results: The mean age of participants was 58.7 years, with 53.8% male and 65.4% having type 2 diabetes. Smoking was present in 38.5% of patients. The analysis revealed that increased HbA1c levels (hazard ratio [HR], 1.22; 95% CI, 1.10-1.35) and smoking (HR, 0.58; 95% CI, 0.40-0.83) were significant predictors of delayed wound healing. Older age (HR, 1.04; 95% CI, 1.02-1.06) was also associated with a longer time to healing. Infection severity did not show a significant impact on healing. Advanced wound care therapies demonstrated a 10% reduction in healing time compared to standard care (p = 0.04). Conclusion: Glycemic control, smoking cessation, and age were significant predictors of wound healing in diabetic foot ulcers. The findings emphasize the importance of managing modifiable risk factors, particularly glycemic control and smoking, to improve healing outcomes in diabetic patients. Advanced wound care therapies were beneficial, but optimal outcomes require comprehensive management addressing lifestyle factors.